Paget's "Seed and Soil" Theory of Cancer Metastasis: An Idea Whose Time has Come. (January 2019) - Akhtar, Mohammed; Haider, Abdulrazzaq; Rashid, Sameera; Al-Nabet, Ajayeb Dakhilalla M.H.
Abstract : The concept that the pattern of metastatic spread of cancer is not random and that cancer cells exhibit preferences when metastasizing to organs, dates back to 1889 when Steven Paget published his "seed and soil" hypothesis. He proposed that the spread of tumor cells is governed by interaction and cooperation between the cancer cells (seed) and the host organ (soil). Extensive studies during the last several decades have provided a better understanding of the process of metastatic spread of cancer and several stages such as intravasation, extravasation, tumor latency, and development of micrometastasis and macrometastasis have been defined. Furthermore, recent studies have shown that the target organs may be prepared for metastatic deposits by the development of premetastatic niches. This specialized microenvironment is involved in promoting tumor cell homing, colonization, and subsequent growth at the target organ. The premetastatic niche consists of accumulation of aberrant immune cells and extracellular matrix proteins in target organs. The primary tumor plays a key role in the development of premetastatic niches by producing tumor-derived soluble factors which mobilize bone marrow-derived hematopoietic cells to the premetastatic niche. Exosomes-derived from the primary tumor also contribute to cancer-favorable microenvironment in the premetastatic niches. These changes prime the initially healthy organ microenvironment and render it amenable for subsequent metastatic cell colonization.